Peningkatan Aktivitas Belajar Siswa pada Materi Membandingkan Pecahan dengan Perkalian Silang Menggunakan Model Pembelajaran Make A Match - Rahamdhon Hasyim (Jurnal Gentala Pendidikan Dasar, 2020)
Mathematics lesson is one of the key subjects, because it is used in almost all subjects. Therefore, learning mathematics in school is important. So also in everyday life it does not escape things related to mathematics. The increase of student learning outcomes in math subjects should begin with the introduction of problems that are appropriate to the situation (contextual problem). Some materials are considered difficult for students, especially in elementary school is the material to compare fractions by cross-multiplication. Many learning models can be used to improve student learning outcomes, with the expectation that teachers using learning models in the learning process will make it easier for teachers to stimulate improved learning outcomes, a systematic and pleksible effort or action to improve student learning capabilities or outcomes. One of the learning models that can be used is to use a make and match. The use of this learning model is expected to increase student learning activities on material comparing fractions by cross-multiplication.